Answer:
A) 1 line of symmetry
Step-by-step explanation:
Answer:
b = 26°
Step-by-step explanation:
a ; b = complementary =>
a + b = 90° } => b = 90° - 64° = 26°
a = 64°
Answer:
a square
Step-by-step explanation:
Answer:
x=0.5355 or x=-6.5355
First step is to: Isolate the constant term by adding 7 to both sides
Step-by-step explanation:
We want to solve this equation: ![2x^2 + 12x - 7 = 0](https://tex.z-dn.net/?f=2x%5E2%20%2B%2012x%20-%207%20%3D%200)
On observation, the trinomial is not factorizable so we use the Completing the square method.
Step 1: Isolate the constant term by adding 7 to both sides
![2x^2 + 12x - 7+7 = 0+7\\2x^2 + 12x=7](https://tex.z-dn.net/?f=2x%5E2%20%2B%2012x%20-%207%2B7%20%3D%200%2B7%5C%5C2x%5E2%20%2B%2012x%3D7)
Step 2: Divide the equation all through by the coefficient of
which is 2.
![x^2 + 6x=\frac{7}{2}](https://tex.z-dn.net/?f=x%5E2%20%2B%206x%3D%5Cfrac%7B7%7D%7B2%7D)
Step 3: Divide the coefficient of x by 2, square it and add it to both sides.
Coefficient of x=6
Divided by 2=3
Square of 3=![3^2](https://tex.z-dn.net/?f=3%5E2)
Therefore, we have:
![x^2 + 6x+3^2=\frac{7}{2}+3^2](https://tex.z-dn.net/?f=x%5E2%20%2B%206x%2B3%5E2%3D%5Cfrac%7B7%7D%7B2%7D%2B3%5E2)
Step 4: Write the Left Hand side in the form ![(x+k)^2](https://tex.z-dn.net/?f=%28x%2Bk%29%5E2)
![(x+3)^2=\frac{7}{2}+3^2\\(x+3)^2=12.5\\](https://tex.z-dn.net/?f=%28x%2B3%29%5E2%3D%5Cfrac%7B7%7D%7B2%7D%2B3%5E2%5C%5C%28x%2B3%29%5E2%3D12.5%5C%5C)
Step 5: Take the square root of both sides and solve for x
![x+3=\pm\sqrt{12.5}\\x=-3\pm \sqrt{12.5}\\x=-3+ \sqrt{12.5}, $ or $x= -3- \sqrt{12.5}\\$x=0.5355 or x=-6.5355](https://tex.z-dn.net/?f=x%2B3%3D%5Cpm%5Csqrt%7B12.5%7D%5C%5Cx%3D-3%5Cpm%20%5Csqrt%7B12.5%7D%5C%5Cx%3D-3%2B%20%5Csqrt%7B12.5%7D%2C%20%24%20or%20%24x%3D%20-3-%20%5Csqrt%7B12.5%7D%5C%5C%24x%3D0.5355%20or%20x%3D-6.5355)
Answer:
B 10/26
Step-by-step explanation:
Cosine is the adjacent side over the hypotenuse.